Tumor Cell Autonomous RON Receptor Expression Promotes Prostate Cancer Growth Under Conditions of Androgen Deprivation()() - Brown, Nicholas E. (Neoplasia, 2018)
Current treatment strategies provide minimal results for patients with castration-resistant prostate cancer (CRPC). Attempts to target the androgen receptor have shown promise, but resistance ultimately develops, often due to androgen receptor reactivation. Understanding mechanisms of resistance, including androgen receptor reactivation, is crucial for development of more efficacious CRPC therapies. Here, we report that the RON receptor tyrosine kinase is highly expressed in the majority of human hormone-refractory prostate cancers. Further, we show that exogenous expression of RON in human and murine prostate cancer cells circumvents sensitivity to androgen deprivation and promotes prostate cancer cell growth in both in vivo and in vitro settings. Conversely, RON loss induces sensitivity of CRPC cells to androgen deprivation. Mechanistically, we demonstrate that RON overexpression leads to activation of multiple oncogenic transcription factors (namely, β-catenin and NF-κB), which are sufficient to drive androgen receptor nuclear localization and activation of AR responsive genes under conditions of androgen deprivation and support castration-resistant growth. In total, this study demonstrates the functional significance of RON during prostate cancer progression and provides a strong rationale for targeting RON signaling in prostate cancer as a means to limit resistance to androgen deprivation therapy.